MEKANISME PENGUNGKAPAN EMISI KARBON DAN REAKSI INVESTOR - Kelvin, Chen; Pasoloran, Oktavianus; Randa, Fransiskus (Jurnal Ilmiah Akuntansi dan Bisnis, 2019)
This research aims to investigate the role of carbon emission disclosure as a mechanism to improve the investors' reaction in the form of abnormal stock returns mediated by cost of equity. The sample used in this study were non-financial companies listed on the Indonesia Stock Exchange from 2013 to 2017 and 122 firms were selected using purposive sampling method. By using path analysis method, the results shows, that the carbon emission disclosure has negative relationship to the cost of equity, carbon emission disclosure has positive relationship to the abnormal stock return and cost of equity has negative and significant relationship to the abnormal stock return. In addition, using Sobel test, the results shows that cost of equity plays a role in mediating carbon emission disclosure to the abnormal stock returns.